Prevalence and associated factors of acute diarrhea among under-five children in Kamashi district, western Ethiopia: community-based study - Adugna Fenta; Kassahun Alemu; Dessie Abebaw Angaw (BMC, 2020)
Abstract Background Diarrheal diseases are the second major cause of death among under-five children globally. It kills about 2.5 million people each year, with 60-70% of them being children under 5 years of age. It is also the second leading cause of morbidity in Ethiopia, with Benishangul Gumuz region bearing burden the highest with 169/1000 under five. This study aimed to determine the prevalence and associated factors of acute diarrhea among under 5 years of age children in Kamashi district, western Ethiopia, 2018. Method A community based cross-sectional study design was used. A two-stage systematic random sampling technique was used to select 8 kebeles and 717 study units. Binary logistic regression model to identify the association between dependent and independent variables. Results The prevalence of acute diarrhea was 14.5% (95% CI: (12.3, 17.3%)). Poor latrine hygiene (AOR = 11.48, 95%CI: 5.64-23.35)), had no handwashing facilities near latrines (AOR = 7.07, 95%CI:3.84-13.03), poor handwashing practice at a critical time (AOR = 5.92, 95%CI: 2.58-13.70), who stored water at home in Jerricans (AOR = 8.6, 95%CI: 1.51-48.84) and complementary feeding before 6 months (AOR = 6.49, 95%CI: 2.01-20.96) had a significant association with acute diarrhea. Conclusion The prevalence of acute diarrhea was still high. Latrine cleanness, availability of handwashing facilities around latrine, hand washing practice at the critical time for handwashing, storage of water by "Jerrican" and time of initiation of supplementary food were the determinant factors of diarrheal diseases.